Five‐year survival outcomes in oropharyngeal squamous cell carcinoma following transoral laser microsurgery. Issue 1 (13th December 2022) - Turner, Brooke; MacKay, Colin; Taylor, S. Mark; Rigby, Matthew Hall
Abstract: Objective: To determine the 5‐year survival outcomes of patients with oropharyngeal cancer treated with transoral laser microsurgery at our institution. Methods: A prospective longitudinal cohort study of all cases of oropharyngeal squamous cell cancer or clinically unknown primaries diagnosed at our institution between September 1, 2014, to December 31, 2019, treated with primary transoral laser microsurgery were analyzed. Patients with a previous history of head and neck radiation were excluded from analysis. Kaplan–Meier survival curves were used to estimate 5‐year overall survival, disease‐specific survival, local control, and recurrence free survival rates in oropharyngeal squamous cell carcinoma. Results: Of 142 patients identified, 135 met criteria and were included in the survival analysis. Five‐year local control rates in p16 positive and negative disease were 99.2% and 100%, respectively, with one locoregional failure in the p16 positive cohort. Five‐year overall survival, disease‐specific survival, and recurrence free survival in p16 positive disease were 91%, 95.2%, and 87% respectively ( n = 124). Five‐year overall survival, disease‐specific survival, and recurrence free survival in p16 negative disease were 39.8%, 58.3%, and 60%, respectively ( n = 11). The permanent gastrostomy tube rate was 1.5% and zero patients received a tracheostomy at the time of surgery. One patient (0.74%) required a return to the OR for a post‐operative pharyngeal bleed. Conclusion: Transoral laser microsurgery is a safe primary treatment option for oropharyngeal squamous cell carcinoma with high 5‐year survival outcomes, notably in p16 positive disease. More randomized trials are needed to compare survival outcomes and associated morbidity in transoral laser microsurgery compared to treatment with primary chemoradiation. Level of Evidence: 3 Abstract : As the incidence of human papilloma virus (HPV) rises, the use of transoral laser microsurgery in the treatment of oropharyngeal cancer is becoming more common, as it allows for good local control and is associated with reduced morbidity. A prospective survival analysis of 135 patients with oropharyngeal squamous cell carcinoma treated with transoral laser microsurgery, found local control rates >99% in HPV‐mediated and non‐mediated disease, with a 1.5% gastrostomy tube dependence rate. Further research is required to better compare survival outcomes in patients treated with transoral laser microsurgery compared to primary radiation.